Toughness improvement of epoxy thermosets with cellulose nanocrystals. Issue 11 (10th June 2021) - Qin, Xiulian; Ge, Wenming; Mei, Honggang; Li, Lei; Zheng, Sixun
Abstract: We report the toughness improvement of epoxy thermosets by the use of cellulose nanocrystals (CNCs). Pristine CNCs were functionalized via surface‐initiated reversible addition–fragmentation chain transfer/macromolecular design via interchange of xanthates (RAFT/MADIX) polymerization. The pristine CNCs were first surface‐treated with 4‐cyano‐4‐(isopropoxycarbonothioylthio)pentanoic chloride and then poly( N ‐vinylpyrrolidone)‐grafted CNCs (CNC‐PVPy) were synthesized with the xanthate‐functionalized CNCs as chain transfer agent. Notably, the as‐obtained CNC‐PVPy can be dispersed into epoxy thermosets in the form of single fibrous nano‐objects, i.e. the nanocomposites of epoxy with CNCs were successfully obtained. The uniform dispersion of CNCs in epoxy matrix is attributable to the compatibilizing effect of PVPy chains. The introduction of CNCs markedly improved the toughness of epoxy thermosets. When the mass fraction of CNC‐PVPy was 30 wt%, the nanocomposites displayed the maximum critical stress intensity factor ( K 1C ) and critical fracture energy ( G 1C ) of 1.76 MN m −3/2 and 0.66 kJ m −2, respectively. The toughening of epoxy thermosets is mainly attributed to the plastic deformation of epoxy matrix, which is initiated from CNCs. © 2021 Society of Industrial Chemistry. Abstract : Cellulose nanocrystals (CNCs) were functionalized via surface‐initiated RAFT/MADIX polymerization, and the as‐obtained poly( N ‐vinylpyrrolidone)‐grafted CNCs (CNC‐PVPy) were used to toughen epoxy thermosets.